Higher Life’s Crucial 9 protects against infertility among U.S. women aged 18–45 years - Huang, Shaoqun; Duan, Shuqin; Choi, Seok; Gong, Hongyang (Frontiers in Endocrinology, 2025)
ObjectiveInfertility is not only a reproductive issue but is also closely linked to cardiovascular health and other factors. Life’s Crucial 9 (LC9) is a set of lifestyle guidelines aimed at improving cardiovascular health, yet its potential association with infertility remains underexplored. This study aims to investigate the relationship between LC9 and infertility, providing new insights and strategies for the prevention and management of infertility.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) from 2013 to 2018. Multivariate logistic regression and weighted quantile sum (WQS) regressions were employed to investigate the association between LC9 and infertility. Restricted cubic spline (RCS) analysis explored the linear or non-linear relationship between LC9 and infertility. Interaction analyses were conducted on subgroups to validate the findings.ResultsThere was a significant negative association between LC9 and infertility. After adjusting for covariates, for every 10-point increase in LC9, there was a 35% decrease in the prevalence of infertility (P < 0.001). This negative correlation persisted when LC9 was divided into quartiles. Moreover, as LC9 increased, there was a trend towards lower infertility prevalence (P for trend < 0.001). WQS analyses showed consistent associations (OR=0.27, 95%CI: 0.14, 0.53), with sleep health score, psychological health score, and Body mass index score as significant factors. The dose-response curve indicated a linear association between LC9 and infertility, with higher LC9 associated with lower infertility risk.ConclusionThe results of this study show a strong negative correlation between LC9 and the prevalence of infertility. Clinically, these findings offer hope for infertility patients, suggesting that adherence to a higher LC9 score significantly reduces the risk of infertility. This will provide a new avenue for infertility prevention and management, offering hope and potential relief to infertile patients.